Penerapan Pengatur Suhu Otomatis pada Kebun Bibit Untuk Ketahanan Pangan Pondok Pesantren Al Mujaddadiyah - Budi Triyono; Yuli Prasetyo; Hanifah N. Kumalaningrum; R. Jasa Kusumo; Basuki Winarno; Aditya PP (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Al Mujaddadiyah Islamic Boarding School has vacant land which is used for nursery. The boarding school nursery is managed by the manager of the boarding school and the students. The boarding school nursery is used to produce plant seeds so that economic benefits are obtained in their management. The problem that exists in the Al Mujaddadiyah Islamic Boarding School Nursery is that plant seeds often dry and wither. This is due to the lack of watering on plant seeds due to the busyness of the cottage manager. Awareness of students to care for and watering plant seeds is also lacking. There is no application of technology to determine the temperature around the nursery to keep it stable. The PKM activity in the nursery school of the AL Mujaddadiyah Islamic boarding school provides solutions to partner problems by setting the temperature automatically in the nursery. The results of this automatic temperature setting can automatically water plant seeds if the temperature in the nursery does not match the initial setting temperature.